Diurnal variations of midlatitude NLC parameters observed by daylight‐capable lidar and their relation to ambient parameters. Issue 24 (18th December 2013) - Gerding, M.; Kopp, M.; Hoffmann, P.; Höffner, J.; Lübken, F.‐J.
<x xml:space="preserve">Abstract</x> [1] Noctilucent Clouds (NLCs) are an important phenomenon of the summer mesopause region. While relatively common in high latitudes, NLCs are sparse (≤10% occurrence rate) below 60°latitude. We present the first study of diurnal variations of midlatitude NLCs based on lidar observations with full diurnal coverage at Kühlungsborn since 2010 independent from solar elevation. Overall, ∼100h of NLCs with a backscatter coefficient of βmax, 532nm>0.5·10−10m−1sr−1are observed within ∼1800h. Occurrence rates decrease regularly from 12% at 5local solar time (LST) to ∼2% at 19LST. The mean NLC brightness varies between ∼1 and ∼3·10−10m−1sr−1with maxima at 4 and 18LST. The simultaneously observed temperatures show a systematic (tidal) variation, but we do not find a direct relation to NLC rates. Comparing NLCs and ambient winds, we find strong indications for the meridional wind (advection) being the main driver for NLC occurrence above our site.